Resource Allocation in Cognitive Cellular Hybrid Network Using Particle Swarm Optimization - Joarder, P; Chatterjee, S (International Journal of Computer Sciences and Engineering, 2025)
Time slot allocation concept for cognitive cellular hybrid network (CCHN) is proposed in this paper. It has been addressed an efficient resource allocation scheme by mitigating interference problem in CCHN. A combination of hybrid underlay-overlay network is introduced to overcome the limitations of underlay and overlay cognitive network. We have adopted an opportunistic cooperative sensing based spectrum access scheme to allocate resource as available time slots among multiple cognitive radio (CR) users. Particle swarm optimization (PSO) algorithm has been implemented to optimize transmitting parameters such as antenna size, modulation index, transmission rate, SNR. In order to achieve the maximum network capacity and proper distribution of time slots beam forming concept of PSO has been utilized. As a result, a new scheme for time slot allocation in cognitive hybrid networks has been adopted. A mathematical model and emulated results have been presented to justify the proposed scheme. The graphical analysis reviles the improvement of throughput performance, system efficiency, transmission rate and the quality of service (QoS) for both the primary and secondary users.